Social and Economic Analysis of Project Management for Foam Glass Production Company Establishment - Ganieva, Guzel Rafikovna; Iskhakova, Dinara Danilovna; Bashirov, Alfred Ildarovich; Kamartdinova, Darya Rafaelovna (International Journal of Criminology and Sociology, 2022)
Currently, much attention is paid to the development of new thermal insulation materials in the production of building materials suitable for use in industrial and residential premises. Foam glass is one of the most popular inorganic thermal insulation materials. Foam glass is considered as one of the most high-quality and durable heat-insulating materials. It has a number of strength characteristics, among which are resistance to deformation, compressive strength, and resistance to environmental influences. Foam glass products are resistant to heat and aggressive chemicals, they do not undergo a combustion process, do not form smoke and do not emit toxic combustion products, and are also resistant to low temperatures. The material is easy to process, which allows you to get products of any desired shape. In this regard, this article discusses the relevance of an enterprise establishment for the production of foam glass: they performed the review of the material properties, environmental friendliness, production methods, and technologies, and analyzed the presence of competitors in the Republic of Tatarstan. The main conclusions on scheduling and social and economic analysis of the planned production are also presented. The purpose of the work is the creation of an enterprise for the production of foam glass. To achieve this goal, it is necessary to analyze the Russian market of heat-insulating materials, research the sales market and draw up a marketing plan, develop a schedule for an enterprise establishment, calculate the economic justification for the proposed production effectiveness, analyze the risks of a project for an enterprise establishment using the sensitivity analysis method.